Chemistry : the molecular nature of matter and change / Martin S Silberberg - Silberberg, Martin S.
A guide to pertinent information for integrating media and extra content into your lecture. It includes: Biological Applications; Engineering Applications; Environmental - Green Chemistry Applications; Organic Chemistry Applications; Demonstrations; Photos, Figures, Tables, and Worked Appearing within the ARIS Presentation Center; and Animations.